Disorder induced polymorphic transitions in the high hydrogen density compound Sr(BH4)2(NH3BH3)2. Issue 46 (14th November 2018) - Jørgensen, Mathias; Lee, Young-Su; Bjerring, Morten; Jepsen, Lars H.; Akbey, Ümit; Cho, Young Whan; Jensen, Torben R.
Abstract : The presence of two stable configurations of the ammonia borane molecule at elevated temperature induces a polymorphic phase transition to lower symmetry. Abstract : The new compound Sr(BH4 )2 (NH3 BH3 )2 has been synthesized and characterized with in situ powder X-ray diffraction and fast (28 or 60 kHz) magic angle spinning 1 H, 11 B and 15 N NMR and structurally optimized with density functional theory calculations. This investigation reveals complex structural rearrangements for this compound as a function of temperature. A room temperature orthorhombic polymorph, α-Sr(BH4 )2 (NH3 BH3 )2, with the space group symmetry Pbca, has been determined with a layered structure of alternating ammonia borane and Sr(BH4 )2, partially stabilized by dihydrogen bonding. Surprisingly the crystal symmetry is lowered upon heating, as evidenced both by in situ synchrotron powder X-ray diffraction and 11 B MAS NMR data, resulting in an intermediate polymorph, β′-Sr(BH4 )2 (NH3 BH3 )2, present from ∼65 to 115 °C. β-Sr(BH4 )2 (NH3 BH3 )2, a sub structure of the β′-polymorph showing higher symmetry with the space group symmetry Aba 2, forms upon further heating. Ab initio molecular dynamics simulations show that the ammonia borane molecule can dynamically alternate between a bidentate and a tridentate coordination to Sr at finite temperature. The dynamic properties of the ammonia borane molecule in the solid state are suggested to cause the observed structural complexity. Based on simultaneous thermogravimetric analysis, differential scanning calorimetry and mass spectrometry, the decomposition of the compound was investigated showing a stabilization of ammonia borane in the structure relative to other metal borohydride ammonia boranes and neat ammonia borane.